31 Tendon Size Increases In Parallel With Tendon Disorganisation: Evidence Of Tendon Remodelling To Maintain Adequate Levels Of Aligned Fibres. (5th September 2014) - Docking, Sean; Cook, Jill
Abstract : Introduction: Increases in tendon dimensions, such as anteroposterior (AP) diameter and cross-sectional area, is a frequently described feature of tendinopathy. Increased AP diameter has been associated with hypoechogenecity on ultrasound suggesting that pathology and tendon thickness are related. 1 Ultrasound changes, an indication of matrix disorganisation, can only be qualitatively interpreted. Ultrasound tissue characterisation, UTC, captures a 3-dimensional image of the tendon and categorises the tendon into four echo-types based on the stability of pixel brightness over contiguous transverse images. 2 The modality removes the reliance on subjective interpretation and quantifies structure into aligned fibrillar structure (echo-type I+II) and disorganised structure (echo-type III+IV). This study investigated the relationship between the amount of disorganised tissue and the size of the Achilles and patellar tendon. The amount of aligned fibrillar structure in a pathological tendon was compared to normal tendon to determine if pathological tendon has a compromised tendon structure. Methods: 91 participants who had their Achilles and/or patellar tendons scanned as part of their clinical management or previous research project were recruited. An algorithm to classify the tendon as normal or pathological was developed based on previously described grey-scale features of tendinopathy (hypoechogenicity, diffuse or whole tendon thickening). Based on UTC algorithms, the total mean cross-sectional area (mCSA), mCSA of aligned fibre structure (echo-type I+II) and disorganised structure (echo-type III+IV) were compared in the pathological and normal tendon using a Mann-Whitney U test. A linear regression between AP diameter, total mean CSA and the mean CSA of disorganised tissue was performed in pathological tendons. Results: As expected, both the pathological Achilles and patellar tendon exhibited significantly larger total mCSA, AP diameter and mCSA of disorganised tissue compared to the normal tendon (p < 0.000). Interestingly, the pathological tendon contained a greater mCSA of aligned fibre structure than the normal Achilles and patellar tendon (p < 0.000) (Figure 1 ). A significant linear relationship was observed between the tendon dimensions and mCSA of disorganised tissue for both the pathological Achilles (R2 = 0.587 and 0.441 for AP and total mCSA, respectively) and patellar tendon (R2 = 0.559 and 0.518 for AP and total mCSA, respectively). Discussion: This study found that tendon dimensions were positively correlated with the amount of disorganisation and that the pathological tendon contained an increased amount of aligned fibrillar structure. In combination, these findings suggest that the pathological Achilles and patellar tendon compensate for an area of disorganisation by increasing tendon dimensions to maintain a sufficient aligned fibrillar structure. A lack of remodelling is not apparent within the pathological Achilles or patellar tendon. Treatments that strengthen the already sufficient levels of aligned fibrillar structure may be better than regenerating areas of disorganisation. References: 1 Malliaras, et al . Scand J Med Sci Sports. 2012;22:149–155 2 van Schie, et al . BJSM . 2010;44:1153–1159